Development Model of Talikor as Cultural Heritage and Ecotourism for Economic Improvement and Cultural Preservation of Duan Lolat - Risakotta, Tesalonika Kezia; Solissa, Hermelina (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
The traditional fishing practice of Talikor is an integral cultural heritage for the Duan Lolat community in the Tanimbar Islands Regency, but it now faces the threat of degradation due to modernization. This research addresses the dual challenges of cultural practice erosion and the need for sustainable economic opportunities for the local community. Its main objective is to develop and empirically validate an integrative model to revitalize Talikor as a sustainable community-based ecotourism initiative. Adopting a mixed-methods design, this study collected data through surveys (N=100), in-depth interviews, and Focus Group Discussions (FGDs). Quantitative data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the causal relationships within the proposed model. The main findings show overwhelming community support, with 95% of respondents agreeing to the development of Talikor ecotourism. The statistically validated model was able to explain 68.89% of the variance in the model's sustainability (R^2 = 0.6889). The strongest causal relationship was identified between Identity Strengthening and Economic Empowerment (β = 0.52, p < 0.001), which underscores the importance of cultural pride as a foundation for economic development. The main contribution of this research is the provision of an empirically validated and community-supported framework that bridges cultural preservation with economic development. This model offers actionable insights for policymakers and development practitioners to revitalize similar cultural heritage as sustainable economic assets.